Identifikasi Kawasan Rawan Bencana Tanah Longsor di Desa Takandeang Kecamatan Tapalang Kabupaten Mamuju: Identification of Landslide-prone Areas in Takandeang Village, Tapalang District, Mamuju Regency - S.M, Fhadly; Ahmad, Asmita; Fauzan Adzima, Ahmad (Jurnal Ecosolum, 2025)
Mamuju Regency is one of the areas in West Sulawesi that has a relatively high potential for landslides on a regional scale. Landslide-prone areas on a village scale have not been widely identified. One of the villages that often experience landslides, which result in fatalities and infrastructure damage, is Takandeang Village, Tapalang District, Mamuju Regency. Determining landslide-prone areas uses a weighting method with parameters: rainfall, soil erodibility, lithology, slope gradient, and land cover. Analysis of soil characteristics: soil erodibility, texture, permeability, and C-organic. Observations of soil structure and macroscopic rocks were conducted directly in the field. The weighting of landslide parameters showed a vulnerability value of 1.2 for rainfall, 0.67 for lithology, 0.6 for soil erodibility, 0.45 for slope gradient, and 0.4 for land cover. Landslide area identification in Takandeang Village shows three classes of vulnerability level, namely low class with an area of 522.86 ha (29%) spread across most of the Takandeang Village Hamlet area, medium vulnerability class with an area of 1115.21 ha (62%) spread across most of the eastern and the western regions of Takandeang Village which are forest areas, and high vulnerability class around 172.09 ha (9%) spread across Takandeang, Salubiru, Limbeng Hamlets, a small part of Benteng Kata, Taloba and Salumati Hamlets. The landslide vulnerability level of Takandeang Village is caused by rainfall as a triggering factor, while lithology and soil erodibility are controlling factors with the same weight in accelerating landslide events.